The Development of Pop-Up Book Learning Media Supported by Technology on Integer Material Based on Type of Children with Special Needs - Saputra, Fahrian Dwi; Lestari, Nurcholif Diah Sri; Murtikusuma, Randi Pratama; Pambudi, Didik Sugeng; Prihandini, Rafiantika Megahnia (Jurnal Pendidikan Matematika, 2025)
Concrete learning media are very important for children with special needs because they can improve understanding through visualization and engaging message delivery. Based on observations at Jember Special School Type C (Education and Care Centre), learning media are rarely used, especially when teaching integer material. This study aims to describe the process and outcomes of developing a pop-up book learning medium tailored to the different types of children with special needs, ensuring its validity, practicality, and effectiveness. The study employs a modified 4-D development model within a Research and Development (R&D) framework. Data were collected through validation sheets, user response questionnaires, interview guides, and learning outcome tests. Three methods of data analysis were used: validity analysis, practicality analysis, and effectiveness analysis. The validation results showed average scores of 3.67, 3.69, and 3.54 for learning media designed for students with intellectual disabilities, physical disabilities, and visual impairments, respectively, which are categorized as valid. The media were then tested on nine students at Jember Special School Type C, consisting of seven students with intellectual disabilities, one student with visual impairment, and one student with physical disability. Practicality analysis was conducted based on student and teacher response questionnaire scores, which were 80.25% and 80.75%, respectively, indicating a good level of practicality. The learning outcome test showed a 100% mastery level, indicating that the learning media met the criteria for effectiveness. This research is expected to serve as a reference for other researchers who wish to develop similar instructional media or further develop pop-up book learning media for other types of children with special needs. Media pembelajaran konkret sangat penting bagi anak berkebutuhan khusus karena dapat meningkatkan pemahaman mereka melalui visualisasi dan penyampaian pesan yang menarik. Berdasarkan observasi di SLB-C TPA (Taman Pendidikan dan Asuhan)  Jember, media pembelajaran jarang digunakan, terutama saat mengajarkan materi bilangan bulat. Penelitian ini bertujuan untuk mendeskripsikan proses dan hasil pengembangan pop -up book sebagai media pembelajaran berdasarkan jenis ABK yang valid, praktis, dan efektif. Penelitian ini menggunakan model pengembangan 4-D yang dimodifikasi dalam kerangka R&D. Pengumpulan data dilakukan melalui lembar validasi, angket respon pengguna, pedoman wawancara, dan tes hasil belajar. Terdapat tiga metode analisis data yaitu analisis kevalidan, analisis kepraktisan, dan analisis keefektifan. Hasil validasi menunjukkan skor rata-rata untuk media pembelajaran tunagrahita, tunadaksa, dan tunanetra sebesar 3,67; 3,69; dan 3,54 yang dikategorikan valid. Media tersebut kemudian diuji coba pada sembilan peserta didik di SLB-C TPA Jember, terdiri dari tujuh peserta didik tunagrahita, satu peserta didik tunanetra, dan satu peserta didik tunadaksa. Analisis kepraktisan dilakukan melalui skor angket respon siswa dan guru yang masing-masing sebesar 80,25% dan 80,75%, menunjukkan tingkat kepraktisan yang baik. Hasil Tes Hasil Belajar menunjukkan ketuntasan belajar sebesar 100%, yang menandakan media pembelajaran telah memenuhi kategori efektif. Penelitian ini diharapkan dapat dijadikan referensi bagi peneliti lain yang ingin mengembangkan media pembelajaran sejenis ataupun mengembangakn media pembelajaran pop-up book untuk anak berkebutuhan khusus lainnya.